Natural selection at work: an accelerated evolutionary computing approach to predictive model selection - Akman, Olcay; Hallam, Joshua (Frontiers in Neuroscience, 2010)
We implement genetic algorithm based predictive model building as an alternative to the traditional stepwise regression. We then employ the Information Complexity Measure (ICOMP) as a measure of model fitness instead of the commonly used measure of R-square. Furthermore, we propose some modifications to the genetic algorithm to increase the overall efficiency.